Experimental investigation of Reed-Solomon error correction technique for wireless sensor network - Cheah, Cheng-Lai; Tan, Poh-Ling; Ho, Chee-Kit * (International Journal of Information and Electronics Engineering, 2014)
In this paper, we propose a Reed-Solomon (RS) error correction code with an error correction capability of 32 bytes for IEEE 802.15.4 wireless sensor network (WSN). This code is chosen based on our experimental investigation and the analysis of error pattern, which revealed that although there are as much as 82% of burst errors out of the total errors are present at WSN, the rate of occurrence of the burst errors decreases when the burst length increases. Experimental results show that the proposed error correction code is able to reduce the packet error rate (PER) significantly for distances shorter than 40 m. At the target PER of 10-3, the proposed technique is able to improve either the transmission distance by about 10 m or the received signal strength indication (RSSI) by about 8 dB compared to the WSN without error correction.